2015
DOI: 10.1371/journal.pone.0125027
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein B48, the Structural Component of Chylomicrons, Is Sufficient to Antagonize Staphylococcus aureus Quorum-Sensing

Abstract: Serum lipoproteins (LP) are increasingly being recognized as dual purpose molecules that contribute to both cholesterol homeostasis and host innate defense. In fact, very low LP levels are associated with increased risk of bacterial infection in critically ill patients. In this respect, we reported that apolipoprotein B100 (apoB100), the 4536 amino acid structural protein of very low density lipoprotein (VLDL) produced by the liver, limits Staphylococcus aureus pathogenesis. S. aureus uses quorum-sensing (QS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 76 publications
2
21
0
Order By: Relevance
“…The general applicability of AIP sequestration was demonstrated by SPR experiments that showed direct binding of oxLDL to immobilized AIP-II or immobilized AIP-IV. Consistent with the generality of this mechanism, it was recently reported that apolipoprotein B100 in VLDL and apoB48 in chylomicrons also inhibit quorum sensing by AIP sequestration (37). Most recently, it was found that mice with hypolipidemia that reduced ApoB levels in their lungs suffered from increased morbidity and inflammation in an S. aureus pneumonia model (38), highlighting the importance of sequestration of AIP by serum lipoproteins as a mechanism of innate immunity.…”
Section: Direct Action Of Serum and Ros On Agr Componentsmentioning
confidence: 72%
See 1 more Smart Citation
“…The general applicability of AIP sequestration was demonstrated by SPR experiments that showed direct binding of oxLDL to immobilized AIP-II or immobilized AIP-IV. Consistent with the generality of this mechanism, it was recently reported that apolipoprotein B100 in VLDL and apoB48 in chylomicrons also inhibit quorum sensing by AIP sequestration (37). Most recently, it was found that mice with hypolipidemia that reduced ApoB levels in their lungs suffered from increased morbidity and inflammation in an S. aureus pneumonia model (38), highlighting the importance of sequestration of AIP by serum lipoproteins as a mechanism of innate immunity.…”
Section: Direct Action Of Serum and Ros On Agr Componentsmentioning
confidence: 72%
“…The details of this mechanism have been unveiled through a series of studies (30,31,37). Initially, it was observed that pooled human serum, but not lipoproteindeficient serum, could inhibit quorum sensing by an agr type I reporter strain during in vitro growth (31).…”
Section: Direct Action Of Serum and Ros On Agr Componentsmentioning
confidence: 99%
“…Since lipoproteins are detectable in lungs shortly after intranasal infection with S. aureus (32) and apoB on LDL binds S. aureus AIP and inhibits agr -activation (23-25), we predicted that decreased circulating lipoprotein levels would result in impaired control of S. aureus QS in the lung. To address this, we compared S. aureus agr -activation in the lungs of mice with reduced apoB levels versus controls.…”
Section: Resultsmentioning
confidence: 99%
“…This in turn leads to expression of over 200 virulence factors (22), many of which are pre- and post-transcriptionally regulated by a small RNA molecule, called RNAIII, produced by transcription from the agr P3 promoter (20, 21). Importantly, apolipoprotein B (apoB), the sole protein component of LDL lipoprotein particles, and not other serum apoproteins or associated lipids, binds and sequesters AIP, thereby inhibiting agr -signaling and limiting pathogenesis during S. aureus skin infection (23-25). However, the impact of apoB deficiency and hypolipidemia on host innate defense in the lung, and against S. aureus pneumonia in particular, has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…ApoB might also contribute to innate defense; studies reported that apoB100 and apoB48 could prevent Staphylococcus aureus (S. aureus) infection by binding and sequestering S. aureus and antagonizing quorum sensing, thereby reducing virulence [35, 36]. …”
Section: Discussionmentioning
confidence: 99%